Asymptomatic Ruptured Sinus of Valsalva Aneurysm Combined with Perimembranous Ventricular Septal Defect, and Bicuspid Aortic Valve in Adult Patient - Lee, Seung Hyun; Kim, Jae Bum; Park, Nam Hee; Kim, Hyung Seop; Keum, Dong Yoon (The Thoracic and Cardiovascular Surgeon, 2013)
We report the case of an adult patient with the unusual combination of a perimembranous (PM) ventricular septal defect (VSD), asymptomatic ruptured sinus of Valsalva communicating with the right ventricle, and a bicuspid aortic valve. Bulged sinus of Valsalva might conceal the small PM VSD, therefore the patient had no symptom-associated VSD until grown up. However, when aortic valve regurgitation associated with prolapsed right aortic cusp worsened and ruptured sinus of Valsalva was found by echocardiogram, the patient underwent aortic valve replacement with anatomical surgical correction of the aortic sinus and VSD.
Keywords: ventricular septal defect; sinus of Valsalva rupture; bicuspid aortic valve